Global outbreaks of respiratory syncytial virus infections from 1960 to 2025: a systematic review and meta-analysisResearch in context - Qiuyao Duan; Jinren Pan; Lin Zheng; Zhiwen Jin; Shijian Li; Hangjie Zhang; Xiaofei Fu; Ren Chen; Zhao Yu; Shunwen Qin; Xiaozhi Xu; Yin Chen; et al. (EClinicalMedicine)
Summary: Background: Respiratory Syncytial Virus (RSV) is a major cause of acute respiratory tract infections (ARTIs) and can trigger outbreaks in vulnerable settings such as nursing homes, pediatric wards, and neonatal intensive care units. This meta-analysis aims to investigate the prevalence, outbreak size, attack rate, and case fatality rate (CFR) of RSV outbreaks reported globally from 1960 to 2025, as well as to assess variations by geographic region, age group, season, outbreak setting, and viral genotypes. Methods: We compiled a global RSV outbreak dataset by searching publications from database inception to January 31, 2025, across MEDLINE, Embase, Global Health, CINAHL, Web of Science, LILACS, OpenGrey, CNKI, Wanfang, and ChongqingVIP. Studies were eligible if they reported data on laboratory-confirmed HRSV outbreaks in any settings (i.e., hospitals, communities, schools, kindergartens, and long-term care facilities) and among all age groups (pediatric and adult patients). There were no language restrictions (English or Chinese). Studies were excluded if they lacked a clear or inconsistent definition or based solely on serology for RSV diagnosis. We used a standardized form to extract publication characteristics, study location, and outbreak and participant information (prevalence, date and season, age, setting, attack rate, CFR, and genotypes). Two authors independently assessed eligibility, with discrepancies being resolved through discussion with a third author. Random-effects models were used to generate pooled estimates with 95% confidence intervals (CIs). The estimated annual percentage change (EAPC) was calculated to assess temporal trends in prevalence, attack rate, and CFR of RSV outbreaks. The study was registered with PROSPERO under CRD42022303015. Findings: A total of 72 articles from 25 countries were included, reporting 82 RSV outbreaks worldwide involving 2282 cases. Among these, 28 studies (reporting 30 outbreaks) provided information on RSV-related deaths, while 32 studies provided RSV genotype information. The highest outbreak rates were observed in Europe, the Americas, and Asia, especially in the winter season. The most common settings were neonatal intensive care units (30.49%), hematology wards/cancer centers (24.39%), and neonatal wards (15.85%). The median outbreak size was 13 cases (range: 3–588), and RSV-B was the most common genotype (46.88%, 15/32). RSV outbreak reporting increased from 3 in 1960–1970 to 37 in 2010–2025, while the overall CFR decreased from 12.29% (95% CI: 2.51–25.95) in the 1990s to 1.24% (95% CI: 0.01–3.73) in 2010–2025 (p < 0.05). The CFRs were the highest among the elderly (9.24%, 95% CI: 2.75–18.07), in hematology wards/cancer centers (7.56%, 95% CI: 2.56–14.15), and in RSV-A and B co-infections (6.31%, 95% CI: 0.02–18.60). The global pooled attack rate was 35.78% (95% CI: 29.16–42.67), higher in children-related outbreaks (42.29%, 95% CI: 34.53–50.23), neonatal wards (44.67%, 95% CI: 31.76–57.92), and RSV-B genotype studies (46.95%, 95% CI: 35.20–58.87). Interpretation: RSV outbreaks have contributed significantly to global morbidity since the 1960s, with increasing reports over time. While the CFRs have decreased, they remain high in certain subgroups based on age, genotype, and outbreak setting. The pooled attack rate remains substantial, particularly in healthcare settings involving RSV-B genotypes and among immunosuppressed populations. This meta-analysis underscores the importance of targeted vaccination and treatment strategies for controlling RSV outbreaks worldwide in the future. Funding: This study was supported by the Zhejiang Provincial Program for the Cultivation of High-Level Innovative Health Talents and Zhejiang Provincial Disease Control and Prevention Administration (2025JK008) and the Key Program of Health Commission of Zhejiang Province/Science Foundation of National Health Commission (WKJ-ZJ-2523).